2020
DOI: 10.1515/sjpain-2020-0023
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the underlying mechanism of pain-related disability in hypermobile adolescents with chronic musculoskeletal pain

Abstract: ObjectivesA significant proportion of adolescents with chronic musculoskeletal pain (CMP) experience difficulties in physical functioning, mood and social functioning, contributing to diminished quality of life. Generalized joint hypermobility (GJH) is a risk factor for developing CMP with a striking 35-48% of patients with CMP reporting GJH. In case GJH occurs with one or more musculoskeletal manifestations such as chronic pain, trauma, disturbed proprioception and joint instability, it is referred to as gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 88 publications
1
20
0
Order By: Relevance
“…fear of failure, fear of injury) and psychological stress in these high performers can induce fear avoidance behavior, which may have influenced maximal performance of individuals with GJH and anxiety. Performance avoidance goals were also observed by Lench et al in participants with high trait anxiety [ 27 ], and a recent review on hypermobile adolescents and young adults proposed that vulnerability to anxiety might cause avoidance behavior as a coping strategy to avoid injury and complaints [ 9 ]. In addition, GJH is highly prevalent in the general child population and considered common during growth [ 28 ].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…fear of failure, fear of injury) and psychological stress in these high performers can induce fear avoidance behavior, which may have influenced maximal performance of individuals with GJH and anxiety. Performance avoidance goals were also observed by Lench et al in participants with high trait anxiety [ 27 ], and a recent review on hypermobile adolescents and young adults proposed that vulnerability to anxiety might cause avoidance behavior as a coping strategy to avoid injury and complaints [ 9 ]. In addition, GJH is highly prevalent in the general child population and considered common during growth [ 28 ].…”
Section: Discussionmentioning
confidence: 93%
“…There have been minimal studies pertaining to disease progression in GJH, h-EDS, and HSD, with the available studies primarily addressing physical functioning [ 8 , 9 ]. In the disease progression of hEDS/HSD from childhood, adolescence, and adulthood roughly three phases are proposed based on cross-sectional observations by Castori et al [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, there have been no EDS proprioceptive studies to date which have included a measure of physical activity in their protocol; we recommend including such a questionnaire in future studies on proprioception in EDS to explore the possibility that physical activity is also a partial predictor of proprioceptive imprecision. It is important to note that a few studies have already found various forms of exercise to be effective in relieving pain, and sometimes any initially observed proprioceptive deficits in those with joint hypermobility [1,6,19], which provides support for the fear-avoidance model proposed by van Meulenbroek et al [18]. It is our impression that each of these theories at least partially explains the proprioceptive deficit observed in our research, and the work of others, but further studies need to be done to fully understand the impact of each of these potential causes on proprioceptive sensitivity in EDS.…”
Section: Localization Precisionmentioning
confidence: 61%
“…Unfortunately, no studies to date have directly linked peripheral nerve damage to deficits in proprioception in this population; we recommend that future studies on nerve damage in EDS incorporate some form of proprioceptive testing to better understand this possibility. Recently, van Meulenbroek et al [18] suggested that the proprioceptive differences commonly seen in adolescents with Hypermobile EDS could be due to physical deconditioning, because of kinesiophobia, since those with joint hypermobility are more prone to injuries and experience pain more intensely than the general population. Unfortunately, there have been no EDS proprioceptive studies to date which have included a measure of physical activity in their protocol; we recommend including such a questionnaire in future studies on proprioception in EDS to explore the possibility that physical activity is also a partial predictor of proprioceptive imprecision.…”
Section: Localization Precisionmentioning
confidence: 99%